Kerja Sama Guru dan Orangtua Guna Menumbuhkan Minat Belajar Pada Pembelajaran PAI Di Kelas III SD Negeri 60 Bengkulu Selatan - Risa Sarpita; Dini Febrini; Masrifa Hidayani (JPT : Jurnal Pendidikan Tematik, 2025)
The title of this research is “Teachers and Parents Cooperation to Grow Interest in Learning in PAI Learning in Class III SD Negeri 60 Bengkulu Selatan. This research is a qualitative research. Data collection techniques obtained through observation, interviews / interviews and documentation. The results of this study indicate that the cooperation between teachers and parents in fostering student interest in learning in PAI subjects at SD Negeri 60 Bengkulu Selatan is quite good, this can be seen from several forms of cooperation that have been carried out by teachers with parents of students in fostering interest student learning in the subject of Islamic Religious Education at SD Negeri 60 Bengkulu Selatan. The author suggests the need for additional collaborative activities as well as providing directions and awareness to parents of students on their duties and responsibilities as educators in informal (family) education, so that with this awareness it can facilitate and strengthen cooperative relationships between teachers and parents and provide improvement on students' interest in learning in Islamic Religious Education subjects at SD Negeri 60 Bengkulu Selatan.